The performance of a solar air heater with conical concentrator under forced convection - Togrul, IT; Pehlivan, D (Elsevier France-Editions Scientifiques Medicales Elsevier, 2003)
In this work, the efficiency of a new solar air heater with a conical concentrator, which can track the sun from sunrise to sunset, was investigated under forced convection conditions of air. The collector, whose absorber was arranged as a two-pass exchanger and mounted on the focal axis of the conical concentrator, was tested for a number of tilting angles and a variety of air mass flow rates. In addition, major operation parameters related to efficiencies of the collector and heat flow in the absorber were determined and correlated with each other and compared with flat-plate solar collectors. The highest efficiencies and maximum increase in the air temperatures were obtained at 28.4degrees tilting and the lowest mass flow rate, respectively. Although, the efficiencies were similar, the maximum outlet temperatures of the air were found to be approximately twice and heat transfer rates inside the absorber were higher than those reached by conventional flat-plate solar air heaters. (C) 2003 Editions scientifiques et medicales Elsevier SAS. All fights reserved.
Keywords: solar air heater; conical concentrator; two-pass collector; heat transfer